Different profiles of lipoprotein particles associate various degrees of cardiac involvement in adolescents with morbid obesity - Siurana, José M.; Sabaté-Rotés, Anna; Amigó, Núria; Martínez-Micaelo, Neus; Arciniegas, Larry; Riaza, Lucia; Mogas, Eduard; Rosés-Noguer, Ferran; Ventura, Paula S.; Yeste, Diego (Frontiers in Pediatrics, 2022)
Introduction: Dyslipidemia secondary to obesity is a risk factor related to cardiovascular disease events, however a pathological conventional lipid profile (CLP) is infrequently found in obese children. The objective is to evaluate the advanced lipoprotein testing (ALT) and its relationship with cardiac changes, metabolic syndrome (MS) and inflammatory markers in a population of morbidly obese adolescents with normal CLP and without type 2 diabetes mellitus, the most common scenario in obese adolescents. Methods: Prospective case-control research of 42 morbidly obese adolescents and 25 normal-weight adolescents, whose left ventricle (LV) morphology and function had been assessed. The ALT was obtained by proton nuclear magnetic resonance spectroscopy, and the results were compared according to the degree of cardiac involvement – normal heart, mild LV changes, and severe LV changes (specifically LV remodeling and systolic dysfunction) – and related to inflammation markers (highly-sensitive C-reactive protein and glycoprotein A [GlycA]) and insulin-resistance (homeostatic model assessment for insulin-resistance [HOMA-IR]). A second analysis was performed to compare our results with the predominant ALT when only body mass index and metabolic syndrome criteria were considered. Results: The three cardiac involvement groups showed significant increases in HOMA-IR, inflammatory markers and ALT ratio LDL-P/HDL-P (40.0 vs 43.9 vs 47.1,p0.01). When only cardiac change groups were considered, differences in small LDL-P (565.0 vs 625.1 nmol/L,p0.07), VLDL size and GlycA demonstrated better utility than just traditional risk factors to predict which subjects could present severe LV changes (AUC: 0.79 [95% CI: 0.54-1]). In the second analysis, an atherosclerotic ALT was detected in morbidly obese subjects, characterized by a significant increase in large VLDL-P, small LDL-P, ratio LDL-P/HDL-P and ratio HDL-TG/HDL-C. Subjects with criteria for MS presented overall worse ALT (specially in triglyceride-enriched particles) and remnant cholesterol values. Conclusions: ALT parameters and GlycA appear to be more reliable indicators of cardiac change severity than traditional CV risk factors. Particularly, the overage of LDL-P compared to HDL-P and the increase in small LDL-P with cholesterol-depleted LDL particles appear to be the key ALT’s parameters involved in LV changes. Morbidly obese adolescents show an atherosclerotic ALT and those with MS present worse ALT values.